City Branding Lamongan Megilan (Qualitative Descriptive Study on City Branding Strategy Planning in Lamongan Regency Government Public Relations to Get Brand Positioning) - Arlinda, Silvi Aris; Kriyantono, Rachmat; Prasetyo, Bambang Dwi (Technium Social Sciences Journal, 2022)
A city is considered to have a strong brand qualification if it has a variety of potential that is worthy of being sold as a tourist and investment destination. Lamongan Regency is considered to have these qualifications, and regional marketing methods are still ineffective and poorly understood by the public. This study aims to see a good Lamongan Regency City Branding planning strategy by exploring all its planning activities, so that the Lamongan Regency City Branding planning process can be consistent. The research method applied is a qualitative type with a constructivist paradigm. The research focus emphasizes planning and meaning (subject perspective). In data collection techniques through interviews and documentation. To determine informants using purposive sampling. Then the data analysis techniques are data collection, data condensation, data presentation, and drawing conclusions/verification. The results of the research show that the Lamongan District Public Relations has carried out all stages of planning the formation of City Branding in Lamongan Regency, in order to achieve the expected image as a Megilan Lamongan Regency by highlighting all the potential of Lamongan Regency to get Brand Positioning.